Creation and the Revelation of God: Interwoven and Interactive Themes across John 1:1–2:12 - Brown, Sherri (Horizons in biblical theology, 2024)
John 1:19–51 provides a bridge from the prologue (1:1–18) into the body of the narrative and the inauguration of Jesus’s public ministry at a wedding feast (2:1–12). The primary theme underlying these opening days has long been debated. Further, do the days articulated by the regular temporal markers tally to six or seven? The evangelist presents the prologue in a chiasm that turns on the pivot of v. 12b. The opening and closing elements correspond to one another (creation imagery in vv. 1–5; revelation imagery in vv. 16–18), but the latter has been fundamentally affected by the pivot: the incarnation of the Word of God and the human response to it. Moreover, as a prologue, its structure and content profoundly affect what follows. Based upon these foundations, this essay argues that themes of both creation and revelation are interwoven and interactive across these early passages.